KMS supplies Puron MBR technology to upgrade UK's Woolston WWTW. Issue 10 (October 2015) - Unknown
Abstract : Koch Membrane Systems Inc (KMS), a developer and manufacturer of membranes and membrane-based filtration systems, has been selected to provide its Puron membrane bioreactor (MBR) modules for the upgrade and expansion of the Woolston wastewater treatment works (WWTW) near Southampton, Hampshire, UK.